Potential associations between chronic whiplash and incomplete spinal cord injury - Smith, AC (Spinal Cord Ser Cases, 2015)
STUDY DESIGN: This research utilized a cross-sectional design with control group inclusion. OBJECTIVES: Preliminary evidence suggests that a portion of the patient population with chronic whiplash may have sustained spinal cord damage. Our hypothesis is that in some cases of chronic whiplash-associated disorders (WAD), observed muscle weakness in the legs will be associated with local signs of a partial spinal cord injury of the cervical spine. SETTING: University based laboratory in Chicago, IL, USA. METHODS: Five participants with chronic WAD were compared with five gender/age/height/weight/body mass index (BMI) control participants. For a secondary investigation, the chronic WAD group was compared with five unmatched participants with motor incomplete spinal cord injury (iSCI). Spinal cord motor tract integrity was assessed using magnetization transfer imaging. Muscle fat infiltration (MFI) was quantified using fat/water separation magnetic resonance imaging. Central volitional muscle activation of the plantarflexors was assessed using a burst superimposition technique. RESULTS: We found reduced spinal cord motor tract integrity, increased MFI of the neck and lower extremity muscles and significantly impaired voluntary plantarflexor muscle activation in five participants with chronic WAD. The lower extremity structural changes and volitional weakness in chronic WAD were comparable to participants with iSCI. CONCLUSION: The results support the position that a subset of the chronic whiplash population may have sustained partial damage to the spinal cord. SPONSORSHIP: NIH R01HD079076-01A1, NIH T32 HD057845 and the Foundation for Physical Therapy Promotion of Doctoral Studies program.